Extracellular Fluid Flow Induces Shallow Quiescence Through Physical and Biochemical Cues - Liu, Bi; Wang, Xia; Jiang, Linan; Xu, Jianhua; Zohar, Yitshak; Yao, Guang (Frontiers in Cell and Developmental Biology, 2022)
The balance between cell quiescence and proliferation is fundamental to tissue physiology and homeostasis. Recent studies have shown that quiescence is not a passive and homogeneous state but actively maintained and heterogeneous. These cellular characteristics associated with quiescence were observed primarily in cultured cells under a static medium. However, cells in vivo face different microenvironmental conditions, particularly, under interstitial fluid flows distributed through extracellular matrices. Interstitial fluid flow exerts shear stress on cells and matrix strain, and results in continuous replacement of extracellular factors. In this study, by analyzing individual cells under varying fluid flow rates in microfluidic devices, we found that extracellular fluid flow alters cellular quiescence depth through flow-induced physical and biochemical cues. Specifically, increasing the flow rate drives cells to shallower quiescence and become more likely to reenter the cell cycle upon growth stimulation. Furthermore, we found that increasing shear stress or extracellular factor replacement individually, without altering other parameters, also results in shallow quiescence. We integrated the experimental results into a mathematical model to gain insight and predict the effects of varying extracellular fluid flow conditions on cellular quiescence depth. Our findings uncover a previously unappreciated mechanism that likely underlies the heterogeneous responses of quiescent cells for tissue repair and regeneration in physiological tissue microenvironments.